Menggagas Fiqh Al-Bī’ah sebagai Basis Etis-Praktis Konservasi Alam - Abdul Quddus (Universitas Islam Negeri Mataram, 2015)
Environmentalists are now seeking a new way to tackle environmental crises after the failure of the science-based approach to these issues. They look for an alternative perspective and mechanism on the basis of religion or wisdom of local tradition for the environment maintenance. Islamic law (fiqh) offers ethical grounds and norms for the conservation of nature. The grounds are not abstract norms but concrete guidance for humans as the God’s vicegerent on earth. Furthermore, fiqh has provided individuals and society the standard of ethic and practice to deal with nature. This article examines the norms and history of fiqh regarding human-nature relations or fiqh al-bī’ah (Islamic law of nature preservation). It shows that fiqh offers a detailed h-hprovision as the scheme of standard consumption, hima (wildlife protection) and ihyā’ al-mawat (cultivation of unowned land). DOI: http://dx.doi.org/10.20414/ujis.v19i1.1258